PENGARUH RELIGIUSITAS, LABEL HALAL, DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN GENERASI MILENIAL MUSLIM - AZIFATUL LAZIFAH; DWI NOVARIA MISIDAWATI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2025)
The development of a halal lifestyle among the millennial Muslim generation has led to increased attention to factors influencing consumer purchasing interest. This study aims to analyze the influence of religiosity, halal labels, and product quality on consumer purchasing interest among millennial Muslim consumers. The research method used is a descriptive qualitative approach with library research, through a review of various academic literature and relevant previous research results. The results of the study indicate that religiosity plays a role in the foundation of values and morals in shaping the consumption attitudes of Muslim consumers, although its influence on purchasing interest is often influenced by other factors. Halal labels have been shown to play a significant role as a guarantee of halalness, safety, and product quality, thereby increasing the trust and purchasing interest of millennial Muslim consumers. Meanwhile, product quality is a dominant factor that significantly influences purchasing interest because it is directly related to consumer satisfaction, trust, and experience. Overall, religiosity, halal labels, and product quality interact in shaping the purchasing interest of millennial Muslim consumers.